Injury risk among athletes on artificial turf: a review of current literature. Issue 5 (8th September 2021) - Sivasundaram, Lakshmanan; Mengers, Sunita; Paliobeis, Andrew; Trivedi, Nikunj N.; Karns, Michael R.; Salata, Michael J.; Voos, James E.
Abstract : Artificial turf is used commonly as an alternative to natural grass for athletic playing surfaces, primarily for its ease of maintenance, multi-use capability year-round, and cost. Prior studies have demonstrated increased biomechanical stresses at the shoe-surface interface on artificial turf when compared to natural grass. However, there is debate whether the altered shoe-surface interface confers additional risk for injury to athletes. The purpose of this study was to review the current literature on injury risk associated with artificial turf among various sports played on turf. The present study was a clinical review of the current literature regarding injury risk on artificial and natural turf. While playing surface generally does not appear to impact overall injury risk in soccer and rugby players, data is inconclusive among American football athletes. Lower-extremity injuries, in particular knee and ankle injuries, more commonly occur on artificial turf in comparison to natural grass. Surface and sport-specific shoes, third-generation artificial turf, and routine monitoring and maintenance have all been shown to reduce the risk of injury on artificial turf. When athletes must play on artificial turf, surface-specific strategies may be implemented to reduce their risk of injury. Future studies should be conducted to evaluate further these risk reduction strategies. Level of Evidence: Level V.